Pengaruh Polyethylene Fiber pada Material Resin Komposit Terhadap Jumlah Koloni Streptococcus mutans - Karina Larasati; Widowati Siswomihardjo; Siti Sunarintyas (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
Fiber reinforced composite (FRC) is a material made of polymer matrix and fiber. Polyethylene fiber is one of the commonly used fiber due its good strength. FRC in the oral cavity will interact with saliva and microorganisms.S. mutans is microorganisms present in oral cavity. The purpose of this study was to determine the effect ofpolyethylene fiber on FRC to S. mutans colony counts. Flowable composite and polyethylene fiber are material used in this study. Bar-shaped samples sized 5 x 4 x 2 mm (n = 4) immersed in 5 mL saliva for 1 hour, then immersed in suspension containing S. mutans and incubated for 24 hours at 37°C. The suspension diluted to 10 then 0.1 mL of the dilution were put in a solid medium and incubated for 48 hours at 37°C. Streptococcus mutans were grown on solid media was determined by direct count. Data were statistically analyzed using unpaired t-test. The results of unpaired t-test showed a significance difference of S. mutans colony between composite resin and FRC with polyethylene fiber (p <0.05). The conclusion from this study was the addition of polyethylene fiber on the composite material significantly increased the number of colonies of Streptococcus mutans.